Impact of Aqueous Extract Artemisia Herba-Alba Leaves as a Green Inhibitor against Acid Activation of 2024 Aluminum Alloy - Nacer Hechiche; Gérald Culioli; Abdelaziz Kadri; Dalila Boughrara; Amar Saal; F. Xavier Perrin (International Journal of Chemical Engineering)
This work is part of the development of new bio-sourced corrosion inhibitors from an abundant resource that can replace conventional synthetic inhibitors that are harmful to both human health and the environment. The corrosion inhibition performance of an aqueous extract of Artemisia herba-alba on the corrosion of 2024 aluminum alloy in a 1 M hydrochloric acid solution is investigated by weight loss method, electrochemical (linear polarization, potentiodynamic polarization, and electrochemical impedance spectroscopy) and SEM techniques. The extract shows excellent corrosion-inhibiting properties on aluminium alloy with a maximum inhibition efficiency of 93% at 0.6 g/L. The adsorption of the natural extract obeys the extended Langmuir isotherm equation adsorption model for multicomponent systems. Temperature studies show that the efficiency of the extract decreases with increasing temperature and that the corrosion activation energies increase in the presence of the extract. Liquid chromatography/high resolution mass spectrometry is used to identify the chemical constituents of the natural extract, and the most abundant phytochemicals for each subclass of metabolite are investigated using density functional theory (DFT) calculations. This study paves the way for further development of a plant that is particularly abundant in the desert regions of North Africa and has until now been used mainly for food for livestock and for pharmaceutical applications.